Adaptive modes of rumination: the role of subjective anger. Issue 3 (3rd April 2017) - Pfeiler, Tamara M.; Wenzel, Mario; Weber, Hannelore; Kubiak, Thomas
ABSTRACT: Rumination has been demonstrated to have negative consequences on affect, behaviour, and physiological markers. Recent studies, however, suggest that distinct "modes" of anger-associated rumination may lead to several positive consequences. Previous research primarily used recall procedures of anger episodes to elicit anger. By contrast, the present study focused on the effect of subjective anger on the process of rumination and tested its effects in a "staged" social interaction where a confederate provoked participants. Subsequently, participants engaged in rumination about the anger-eliciting event either in an abstract-distanced or a concrete-immersed rumination mode. Results showed an adaptive effect of abstract-distanced rumination on subjective anger primarily if anger is high prior to rumination. The findings also suggest different self-reported anger-related coping strategies in response to subjective anger intensity. These findings highlight that an abstract-distanced rumination may have differential effects on affective outcomes and anger-related coping strategies.